Pengembangan Media Pembelajaran Interaktif Berbasis Android Pada Materi Buddha Parinibbana Kelas 9 Sekolah Menengah Pertama - Aleks Effendi; Partono Nyanasuryanadi; Eko Prasetyo (Journal on Education, 2023)
The object of this research is the development of android-based interactive learning media in the subjects of Buddhist Religion and Moral Education. Especially on Buddha Parinibbana material. Learning in the subjects of Buddhist Religion and Moral Education at SMPN 1 Cluwak still uses conventional methods, namely lectures which are considered ineffective. This research seeks to solve these problems. This research is research development or research and development (R&D). The method used in this research is a 10-step method developed by Borg and Gall (1889). This research only took four stages due to limited ability, time and cost. The results of this study are in the form of learning media products in the form of applications using the Android operating program. The material in the application is Buddha Parinibbana in grade 9 of junior high school.